Evaluating angles of tunnel projection in post reconstruction of anterior cruciate ligament injury: A radiological and International Knee Documentation Committee Score correlation study - Nugroho Rendra Praliestyo; Hernugrahanto Kukuh Dwiputra; Utomo Dwikora Novembri; Widhiyanto Lukas (Scripta Medica)
Background/Aim: The tunnel placement angles accuracy in reconstruction of anterior cruciate ligament (ACL) injury with single bundle graft was critical for reviving function and knee stability. Radiological X-rays could provide reliable metric to predict ACL success. The aim of this research was to review the connection among tunnel of tibiofemoral inclination angles, measured through radiological (X-ray) imaging and functional result as appraised by the International Knee Documentation Committee (IKDC) score. Methods: A retrospective study was conducted on patients with reconstruction of ACL injury with single bundle graft. Radiographic images were used to measure the femorotibial tunnel inclination angles post-surgery. IKDC scores were collected to assess knee function and patient outcomes. Statistical analysis was done to evaluate the correlation between tunnel projection angles and IKDC scores. Results: The study included 60 number of patients. The average IKDC score was 73.3 %, with 17 samples having an IKDC score > 75 % and 43 samples having an IKDC score < 75 %. Statistical analysis showed that the Bernard-Hertel percentage was significantly related to the IKDC score (p = 0.05). Patients with tunnel angles within the optimal range demonstrated higher IKDC scores, indicating better knee function and stability. Conclusion: Accurate femorotibial tunnel placement in ACL reconstruction, as assessed through radiological imaging, is associated with improved functional outcomes. This study highlights the importance of precise surgical technique in optimising patient recovery and knee function post-ACL reconstruction.